The WD40-Protein PfWLP1 Ensures Stability of the PfCCp-Based Adhesion Protein Complex in Plasmodium falciparum Gametocytes - Roling, Lena; Flammersfeld, Ansgar; Pradel, Gabriele; Bennink, Sandra (Frontiers in Cellular and Infection Microbiology, 2022)
Members of the WD40-repeat protein family can be found in all eukaryotic proteomes where they usually serve as interaction platforms for the assembly of large protein complexes and are therefore essential for the integrity of these complexes. In the malaria parasite Plasmodium falciparum, the WD40-repeat protein PfWLP1 has been shown to interact with members of distinct adhesion protein complexes in the asexual blood stages and gametocyte stages. In this study, we demonstrate that the presence of PfWLP1 is crucial for both the stability of these gametocyte-specific adhesion complexes as well as for gametocyte maturation and gametogenesis. Using reverse genetics, we generated a PfWLP1-knockdown parasite line for functional characterization of the protein. Knockdown of PfWLP1 resulted in a slight reduction of gametocyte numbers and significantly the impaired ability of the gametocytes to exflagellate. PfWLP1-knockdown further led to reduced protein levels of the Limulus coagulation factor C-like (LCCL)-domain proteins PfCCp1 and PfCCp2, which are key components of the adhesion complexes. These findings suggest that the interaction of PfWLP1 with members of the PfCCp-based adhesion complex ensures complex stability and thereby contributes to gametocyte viability and exflagellation.